High dimensional object rearrangement for a robot manipulation in highly dense configurations - Lee, Jinhwi; Rakhman, Ulzhalgas; Nam, Changjoo; Kang, Seunghyun; Park, Jonghyeon; Kim, ChangHwan (Springer Verlag, 2022)
We propose a Task and Motion Planning algorithm for a robot manipulator to rearrange objects in a narrow and highly-dense workspace. In such a workspace, there may not be enough space to rearrange the objects that obstructs the way for a robot manipulator to access a target object. The present work aims to relocate as few objects (so called obstacles) as possible for the robot manipulator to grasp the target object successfully. The proposed algorithm seeks both the sequence of obstacles to be rearranged and the corresponding places to move them. A heuristic search is employed to find a rearrangement sequence and places. Especially, in the proposed algorithm, stacking an object on the top of other objects is allowed, while searching a place to rearrange obstacles. Virtual simulations and real robot experiments show that the proposed algorithm works reasonably for dense real-world environments.